2019
DOI: 10.21470/1678-9741-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Involvement in Behçet's Disease: what are its Risks and Prognosis? (Rare Cases and Literature Review)

Abstract: Objective In our clinic, we aimed to investigate the effect of preoperative risk factors and postoperative complications on reoperation and mortality in cases with Behçet's disease which presents very rare coronary artery involvement.Methods Thirteen patients with Behçet's Disease who had undergone coronary artery bypass grafting in our center between 2003 and 2015 were analyzed. We evaluated the clinical and laboratory findings, complications and mortality rates of our patients in light of the literature.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
(38 reference statements)
0
14
0
1
Order By: Relevance
“…The high prevalences of peripheral venous thrombosis (20%) and arterial thrombosis (10%) presented in table 1 were compatible with Vural’s study in Turkey. 20 Furthermore, our study revealed a higher prevalence of coronary artery thrombosis in AMI among the uveitis group than in the non-uveitis group, implying tendency to thrombosis could also be related to the occurrence of AMI, especially in the uveitis group.…”
Section: Discussionmentioning
confidence: 46%
“…The high prevalences of peripheral venous thrombosis (20%) and arterial thrombosis (10%) presented in table 1 were compatible with Vural’s study in Turkey. 20 Furthermore, our study revealed a higher prevalence of coronary artery thrombosis in AMI among the uveitis group than in the non-uveitis group, implying tendency to thrombosis could also be related to the occurrence of AMI, especially in the uveitis group.…”
Section: Discussionmentioning
confidence: 46%
“…Vascular involvement is seen in 7%–38% of cases with a high mortality in severe affliction. [ 4 5 ] Interestingly, there is a greater predilection of the venous system compared to arterial involvement. Cardiac involvement can be life-threatening and has been reported variably anywhere between 1% and 16%.…”
Section: Discussionmentioning
confidence: 99%
“…This happens along with a disequilibrium of scavenging enzymes which eventually leads to destructive effects [15]. Indeed, vasorum occlusion and transmural necrosis in the walls of the large muscular arteries ensues leading to deterioration of blood flow and then degeneration of vessel wall [28,29].…”
Section: Pathophysiology Histopathologymentioning
confidence: 99%
“…Thromboembolism mainly triggered by endothelial dysfunction is also a characteristic finding in BD, so endothelium-dependent flow-mediated dilation is diminished causing therefore an increase in vascular inflammation. Furthermore, the associated thrombin and fibrin release and decreased fibrinolysis [28,30] will eventually lead to heart and vessel lesions [31,32].…”
Section: Pathophysiology Histopathologymentioning
confidence: 99%
See 1 more Smart Citation